New conjugated polymers : Synthesis, characterisation and applications - Maier, Stefanie (Trinity College (Dublin, Ireland). School of Physics, 2000)
A series of conjugated polymers related to poly (phenylenevinylene) have been synthesised and characterised. These polymers contain various substitution patterns. Octyloxy side-chains were attached to the arylene units of the polymer backbone for solubility reasons.
Keywords: Physics, Ph.D.; Ph.D. Trinity College Dublin